FILSAFAT ANALITIS MENURUT LUDWIG WITTGENSTEIN: Relevansinya bagi Pengembangan Filsafat Bahasa(Analytical Philosophy ofLudwig Wittgenstein: Its Relevance To the Development of Language Philosophy) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT The objective of the research are to describe the analytic philosophical thoughts of Ludwig Wittgenstein consisting of (1) the ontological aspect that includes the essence of a language reality, the essence of the world, the mean¬ing of name, formal concept, real concept, the limit of language, and picture theory. (2) The epistemological aspect that includes the essence of proposi¬tions, the essenc of the truth language expression, language logic, philo¬sophical method and grammatical investigations. (3) The axiological aspect that include the values contained in the expressions of a language and its function. (4) The relevance of the development of language philosophy. The result of the research show that Wittgenstein's thoughts are classi¬fied into two periods, i.e.: the first period of Tractatus Logico-Philosophicus (1922), wich the core of the first is the picture theory and language logic. According to Wittgenstein the essence of the language is the logical picture of the empirical world and made of propositions that represent a state of affairs. The first period of his philosophy influences the logical positivism. The second period of Hie Philosophical Investigations (1953), contains language games. According to Wittgenstein a language is used by human being in various areas of life that are governed by the rules of each of the areas. The philosophical thoughts of the second period influences the ordi¬nary language philosophy and postmodernism. Wittgenstein's thoughts are relevance to the development of a language philosophy. The principles of language game are relevance to the develop¬ment of "language axiology" and "grammatical theology". KeyWords: picture theory - analytic philosophy - language game - proposition ABSTRACT The objective of the research are to describe the analytic philosophical thoughts of Ludwig Wittgenstein consisting of (1) the ontological aspect that includes the essence of a language reality, the essence of the world, the mean¬ing of name, formal concept, real concept, the limit of language, and picture theory. (2) The epistemological aspect that includes the essence of proposi¬tions, the essenc of the truth language expression, language logic, philo¬sophical method and grammatical investigations. (3) The axiological aspect that include the values contained in the expressions of a language and its function. (4) The relevance of the development of language philosophy. The result of the research show that Wittgenstein's thoughts are classi¬fied into two periods, i.e.: the first period of Tractatus Logico-Philosophicus (1922), wich the core of the first is the picture theory and language logic. According to Wittgenstein the essence of the language is the logical picture of the empirical world and made of propositions that represent a state of affairs. The first period of his philosophy influences the logical positivism. The second period of Hie Philosophical Investigations (1953), contains language games. According to Wittgenstein a language is used by human being in various areas of life that are governed by the rules of each of the areas. The philosophical thoughts of the second period influences the ordi¬nary language philosophy and postmodernism. Wittgenstein's thoughts are relevance to the development of a language philosophy. The principles of language game are relevance to the develop¬ment of "language axiology" and "grammatical theology".